ALTY - Husin, Muhammad; Musa, Muhammad Zamuren; Amiruzam, Nurul Husna (2010)
In a fire, the important thing is to avoid smoke inhalation! It can cause you to pass out before getting to safety. It can cause permanent damage to lungs and airways; Alty Safety.